2021
DOI: 10.3390/rs13183635
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Ocean Currents from Sea Surface Temperature Observations: The Catalan Sea (Western Mediterranean)

Abstract: Current observations of ocean currents are mainly based on altimetric measurements of Sea Surface Heights (SSH), however the characteristics of the present-day constellation of altimeters are only capable to retrieve surface currents at scales larger than 50–70 km. By contrast, infrared and visible radiometers reach spatial resolutions thirty times higher than altimeters under cloud-free conditions. During the last years, it has been shown how the Surface Quasi-Geostrophic (SQG) approximation is able to recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To confirm this answer it would be necessary to analyze global numerical simulations (Su et al., 2020) or observations (Merchant et al., 2019). However, before using infrared SST measurements, it is necessary to address the problems generated by data gaps due to cloud coverage (Isern‐Fontanet et al., 2021); the masking out of strong fronts by the failure of cloud mask algorithms (Kilpatrick et al., 2019); and the changes in Δ h − induced by noise (Isern‐Fontanet & Hascoët, 2014). Among them, the most critical problem is the masking of strong fronts because it has a direct impact on the estimation of h ∞ and thus, Δ h − = h d − h ∞ .…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this answer it would be necessary to analyze global numerical simulations (Su et al., 2020) or observations (Merchant et al., 2019). However, before using infrared SST measurements, it is necessary to address the problems generated by data gaps due to cloud coverage (Isern‐Fontanet et al., 2021); the masking out of strong fronts by the failure of cloud mask algorithms (Kilpatrick et al., 2019); and the changes in Δ h − induced by noise (Isern‐Fontanet & Hascoët, 2014). Among them, the most critical problem is the masking of strong fronts because it has a direct impact on the estimation of h ∞ and thus, Δ h − = h d − h ∞ .…”
Section: Discussionmentioning
confidence: 99%
“…To enrich the information given by the radars, we explore the feasibility of using chlorophyll-a (Chl-a) and sea surface temperature estimation in the region as tracers for the surface circulation. In fact, satellite-derived data provide an excellent tool for identifying circulation patterns at fine spatial and temporal resolution and several studies demonstrated the potential of ocean color and SST data to extract valuable information for tracking mesoscale and submesoscale features (e.g., [45][46][47][48][49][50]).…”
Section: Aim Of the Workmentioning
confidence: 99%
“…In 2006, it was proposed to use the Surface Quasi-Geostrophic (SQG) theory to obtain estimations of subsurface dynamics from satellite measurements [46,47]. The validity of this approach was tested using infrared SST [48][49][50]; microwave [51,52]; and SSS [53] measurements. The main conclusion was that the SQG approach is better suited to reconstruct the ocean dynamics in the upper 500 m for energetic areas with deep mixed layer depths (MLD) [46,47,52,54,55].…”
Section: Introductionmentioning
confidence: 99%